I do not want to go to the hospital again. Issue 3 (16th February 2019) - Butman, Samuel M.; Paris, Raelene
Key Points: Readmission after myocardial infarction is not uncommon. The likely readmission patient is by and large predictable. Coronary interventions appear to reduce the rate of readmissions.